Vagus Nerve Stimulation for Depression: A Systematic Review - Lv, Hang; Zhao, Yan-hua; Chen, Jian-guo; Wang, Dong-yan; Chen, Hao (Frontiers in Psychology, 2019)
Background: Depression is a common mental disorder worldwide. Psychological treatments and antidepressant medication are the usual treatments for depression. However, a large proportion of patients with depression do not respond to the treatments. In 2005, Vagus nerve stimulation was approved for the adjunctive long-term treatment of chronic or recurrent depression in adult patients experiencing a major depressive episode who had failed to respond to four or more adequate antidepressant treatments. However, the efficacy of VNS for treating depression remains unclear. Accordingly, we performed a systematic review to evaluate the efficacy and safety of VNS. Methods: We conducted a systematic review in accordance with the Cochrane Handbook for Systematic Reviews of Interventions. Systematic search was performed in the database of Pubmed, Embase, CENTRAL, and Web of science for identifying the suitable trials. Suicidal rate was considered as the primary outcome in this review. Result: Only two randomized sham controlled add-on studies including 255 cases (134 with VNS treatment and 121 control cases) were included in this review. None of the studies reported suicidal rate. We performed a qualitative analysis and it is suggested that there was no significant statistic difference between VNS and sham VNS on the score of 24-item Hamilton Rating Scale for Depression (HAMD24) (MD: −2.40, 95% CI: −7.90 to 3.10). Similar findings were also reported on improvement percentage of HAMD24 (MD: 1.00, 95%CI: −6.06 to 8.06), Montgomery-Asberg Depression Rating Scale (MADRS) (MD: 4.70, 95%CI: −2.98 to 12.38) and 30 item Inventory of Depressive Symptomalogy-Self-Report (IDS-SR30) (MD: 4.9, 95%CI: −1.89 to 11.69). However, a marginal difference of Beck Depression Inventory self-rating score was detected between the real and sham treatment (MD: 7.80, 95% CI: 0.34 to 15.26). Aminor effect of IDS-SR30was also found in real VNS group (RR: 2.33, 95% CI: 1.07 to 5.10). Conclusion: The efficacy and safety of VNS for depression is still unclear. Further randomized controlled trials are needed to confirm the efficacy and safety of VNS.